Incidence, delays, and outcomes of STEMI during COVID‐19 outbreak: Analysis from the France PCI registry. Issue 6 (23rd November 2020) - Rangé, Grégoire; Hakim, Radwan; Beygui, Farzin; Angoulvant, Denis; Marcollet, Pierre; Godin, Matthieu; Deballon, Ronan; Bonnet, Philippe; Fichaux, Olivier; Barbey, Christophe; Viallard, Louis; Lesault, Pierre Francois; et al.
Abstract: Objectives: The aim of this study was to assess the impact of the coronavirus disease 2019 (COVID‐19) outbreak on incidence, delays, and outcomes of ST‐elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PPCI) in France. Methods: We analyzed all patients undergoing PPCI <24 hours STEMI included in the prospective France PCI registry. The 2 groups were compared on mean monthly number of patients, delays in the pathway care, and in‐hospital major adverse cardiac events (MACE: death, stent thrombosis, myocardial infarction, unplanned coronary revascularization, stroke, and major bleeding). Results: From January 15, 2019 to April 14, 2020, 2064 STEMI patients undergoing PPCI were included: 1942 in the prelockdown group and 122 in the lockdown group. Only 2 cases in the lockdown group were positive for COVID‐19. A significant drop (12%) in mean number of STEMI/month was observed in the lockdown group compared with prelockdown (139 vs 122, P < 0.04). A significant increase in "symptom onset to first medical contact" delay was found for patients who presented directly to the emergency department (ED) (238 minutes vs 450 minutes; P = 0.04). There were higher rates of in‐hospital MACE (7.7% vs 12.3%; P = 0.06) and mortality (4.9% vs 8.2%; P = 0.11) in the lockdown group but the differences were not significant. Conclusion: According to the multicenter France PCI registry, the COVID‐19 outbreak in France was associated with a significant decline in STEMI undergoing PPCI and longer transfer time for patients who presented directly to the ED. Mortality rates doubled, but the difference was not statistically significant.